(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
The water-to-cement ratio (w/c ratio) is a critical parameter in the formulation of mortar and concrete. The w/c ratio is a fundamental factor that significantly affects the performance and properties of the final product. This study investigated the influence of different w/c ratios and curing conditions on concrete properties. The preliminary test was conducted on coarse and fine aggregate by complying with ASTM C33. The concrete proportion ratio of 1:2:4 was adopted by mixing with various amounts of distilled water to create ratios of 0.5, 0.6, 0.7, and 0.8. The hardened concretes were divided into two types of curing conditions (pond curing and burlap curing). Compressive strength, sorptivity, and carbonation tests were conducted by complying with the concrete’s standard procedure to determine the concrete's properties. This research has revealed that a higher w/c ratio contributes to higher porosity and negatively impacts its strength. The higher w/c ratio has decreased compressive strength and increased water filtration (sorptivity) and carbon dioxide ingression (carbonation). Based on the results, lower w/c ratio with pond curing showed better concrete physical and chemical properties at 28th days.